The complete mitochondrial genome sequences of Phlebopus portentosus and Leccinum extremiorientale (Boletales; Boletinellaceae: Phlebopus; Leccinum) - Yun Huang; Fen Zhang; Li-Zhi Gao (Mitochondrial DNA. Part B. Resources)
In this study, the complete mitochondrial genomes of Phlebopus portentosus and Leccinum extremiorientale were first sequencedusing the PacBio sequencing platform. We assembled circular mitogenomes of P. portentosus (57,307 bp) and L. extremiorientale (45,100 bp), with AT contents of 78.43% and 76.85%, respectively. Phylogenetic analysis revealed that P. portentosus and L. extremiorientale formed a well-supported clade with Tylopilus brunneirubens and Suillus huapi within the Boletales. This study provides high-quality reference genomes for future domestication and genetic breeding programs of P. portentosus and L. extremiorientale.